Processing of quick cooking rice using three high amylose rice varieties - Maceda, Gerald John A.
The laboratory production of quick cooking rice was done using three test rice varieties namely: IR 42; 36; and 74. Hydration using a 1:1 mixture of 0.5% sodium citrate and 0.5% calcium chloride maintained at 50°C for 15 min showed moisture ratio and volume ratio values ranging from 1.37-1.48 and 1.17-1.22, respectively. Optimum gelatinization conditions using steam under pressure at 15 psi for 2 min were establish with water ratio of 1:1.0, 1:1.0 and 1:0.8 for the variety IR 42, 36 and 74, respectively. These conditions resulted to 100% gelatinization of the rice samples with minimum clumping and breakage. Convective air drying, freeze drying and combination freeze and convective drying resulted to drying times in the range of 0.75-3.0 h for to attain 10% moisture content in QCR products. Rehydration by soaking in water maintained at 60-70°C for 15 min resulted to moisture uptake, volume ratio, percent clumpiness and breakage values ranging from 2.28-5.13, 1.46-3.28, 0-5% and 6-25%, respectively. The moisture ratio, volume ratio, percent clumping and breakage values of the QCR samples rehydrated by boiling in water at 100°C for 5 min ranged from 1.90-5.99, 1.33-3.48, 0-5% and 0-25%, respectively. Variations in quality of the rehydrated samples was attributed to varying gelatinization temperature characteristics of the samples. The study recommends to evaluate the storage stability of the QCR products produced.